Development of a Digital Learning Platform to Improve Math Problem Solving Skills - Yuliza, Nova; Herpratiwi, Herpratiwi; Firdaus, Rangga; Fitiriawan, Helmy (UNDIKMA, 2025)
Mathematical problem solving skills are not only limited to the ability to work on routine or algorithmic problems, but also include the ability to solve non-routine problems, which require creativity, logic, and more complex thinking strategies. The researcher's findings that students' mathematical problem solving skills are very low can be seen from learning documents and the use of learning media that tends to be conventional. For this reason, this study aims to develop a digital learning platform to improve students' math problem solving at MTsN 1 Pesawaran. This research is a development research using the ADDIE approach model, the research sample used amounted to 30 students who will be observed using 20 items of assessment instruments to determine the problem solving ability of students. Data analysis in this study used the N-Gain formula to determine the effectiveness of the development of digital learning platforms. The results of the study can be concluded that the digital learning platform obtained 100% significant results with very effective interpretation on students' math problem solving at MTsN 1 Pesawaran. The development and selection of mathematics learning instructional design to improve students' mathematical problem solving is achieved very effectively